Utilization of Modified Indonesia Natural Bentonite for Dye Removal - Harish Reza Septiano Warsono; Winarto Kurniawan; Hirofumi Hinode (ASEAN Journal of Chemical Engineering, 2019)
Bentonite is clay mineral with many applications such as adsorbent, ion exchanger or catalyst support. Indonesia possesses high quantity of natural bentonite reserves, however, due to the limited knowledge about its properties and potential applications, the utilization is still not yet fully maximized. To address this problem, this research aimed to characterize the properties of Indonesian natural bentonite and study its capability in removing dye pollutants as an alternative application of Indonesian natural bentonite. Characterization of Indonesian natural bentonite was successfully conducted and the result showed that it had adequate properties to be utilized. Further modification with pillaring treatments using Al, Cu, Mn, and Ti were also successfully done to intercalate the metal pillaring agent into the bentonite bulk. Dye pollutants removal test showed that Indonesian natural bentonite and its modified forms were able to remove some dye pollutants from aqueous water system. The removal of the dyes was mainly influenced by the charge of the dyes as well as the pore size of the bentonites samples. Study on the influence of pH showed that cationic dye removal was promoted at high pH, while the removal of anionic dyes were promoted at low pH.